On the Problem of Will and Self-Regulation in Cultural-Historical Psychology - E.O. Smirnova (Культурно-историческая психология, 2015)
This paper attempts to differentiate between the concepts of 'will' and 'selfregulation'. Basing on literature research the author presumes that here we deal with two qualitatively different and specific processes: one of them centers around the awareness of an individual's actions, while at the core of the other lies the impulse to act, i.e. motivation. Thus the author sets forth a hypothesis that will and selfregulation have very different psychological content and different lines of development in ontogenesis. Following L.S. Vygotsky, the author considers selfregulation as the ability to control oneself (one's inner and outer activity) with the help of culturally provided means of organizing behavior. Stages of selfregulation development are therefore shaped by the level of the individual's awareness of his/her activity and by the means employed for its organization. Will, as it has been interpreted over the course of history, is considered as the urge towards active actions, as the powerfulness and persistence of one's wishes and desires (volitions). From this perspective the development of will way be described as the formation of persistent motivation in a child, as the emergence of his/her own desires. The paper reveals the relationship between impulse and awareness in various forms of child activities suggesting that, however specific, will and selfregulation are one in their genesis. The final part discusses issues in modern childhood related to the development of will and selfregulation